Brand name and country-of-origin effects on consumers in Malaysia - Neoh, Chee Yeong (2004)
In the marketing literature, the influence of country-of-origin on the evaluation of products has been studied for decades and it have some impact on purchase intentions. However, nowadays products are typically designed in one country, manufactured in another and assembled elsewhere which led to the proliferation of ‘hybrid products’. Therefore, there are new literatures on country-of-origin of brand because of country-of-origin has become confusing as consumer are not able to tell the country of assembly or country of product design of product. Consumer Ethnocentric Tendencies (CETSCALE) has become a critical explanatory variable. It represents the beliefs held by consumers about the appropriateness of purchasing foreign products and it is believed to have impact on consumer preference.